Only One Earth : the Long Road via Rio to Sustainable Development. - Dodds, Felix (Taylor and Francis, 2012)
Forty years after the United Nations Conference on the Human Environment in Stockholm, the goal of sustainable development continues via the Rio+20 conference in 2012. This book will enable a broad readership to understand what has been achieved in the past forty years and what hasn't. It shows the continuing threat of our present way of living to the planet. It looks to the challenges that we face twenty years from the United Nations Conference on Environment and Development, "The Earth Summit," in Rio, in particular in the areas of economics and governance and the role of stakeholders.